2018
DOI: 10.1093/jmcb/mjy058
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of ACAP4 regulates CCL18-elicited breast cancer cell migration and invasion

Abstract: Tumor metastasis represents the main causes of cancer-related death. Our recent study showed that chemokine CCL18 secreted from tumor-associated macrophages regulates breast tumor metastasis, but the underlying mechanisms remain less clear. Here, we show that ARF6 GTPase-activating protein ACAP4 regulates CCL18-elicited breast cancer cell migration via the acetyltransferase PCAF-mediated acetylation. CCL18 stimulation elicited breast cancer cell migration and invasion via PCAF-dependent acetylation. ACAP4 phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Similarly, in the Bev arm, pulmonary and activation‐regulated cytokine (PARC) serum levels (chemokine [C‐C motif] ligand 18 [ CCL18 ], a cytokine involved in breast cancer cell invasion; Supplementary Figs. S1 a –S1 c ) and endothelial cell protein C receptor (ePCR) levels (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the Bev arm, pulmonary and activation‐regulated cytokine (PARC) serum levels (chemokine [C‐C motif] ligand 18 [ CCL18 ], a cytokine involved in breast cancer cell invasion; Supplementary Figs. S1 a –S1 c ) and endothelial cell protein C receptor (ePCR) levels (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that ezrin and its interaction partner ACAP4 acetylation is involved in breast cancer metastasis in response to cytokine CCL18 stimulation 32,58 . Given the hyper-activation of Aurora kinase activity in HCC 59 , acetyl-phosphorylation cross-talk on the regulation of cellular dynamics 60 , it would be of great interest to delineate the spatiotemporal dynamics of ezrin acetylation and ROCK2-mediated phosphorylation in HCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic phosphorylation liberates TTK/Mps1 coacervates from the kinetochore and promotes its cytoplasmic distribution. Since amplification of TTK/Mps1 promotes breast cancer progression, and inhibition of TTK/Mps1 kinase activity leads to improved outcomes in clinical oncology (90), it would be of interest to determine whether TTK/Mps1 forms coacervates with its chemical inhibitor at the kinetochore and whether coacervates at the kinetochore are involved in the underlying mechanism for interrogation of breast cancer progression (91,92). Pelkmans and colleagues show that another mitotic dual kinase, DYRK3, regulates membraneless organelles by preventing un-mixing of the cytoplasm into aberrant organelles during mitosis (93), indicating that, during cell division, the kinase activities of Mps1 and DYRK3 control the LLPS.…”
Section: Aberrant Llps and Chromosome Instabilitymentioning
confidence: 99%